Contamination by microorganisms in the various types of cutting boards (Research, Society and Development, 2021)
In the handling of various foods, contamination can occur due to the irregular way in which utensils are handled, increasing the risk of transmission of microorganisms from one food to another. In most cases, contamination occurs due to inadequate sanitation. Cutting boards in the kitchen are widely used, and this utensil, with the accumulation of cuts, recesses and holes, becomes a hospitable place for the proliferation of microorganisms; glass, plastic and wood boards are the most used, but the one with the greatest risk of contamination is wood. This research aims to identify the level of contamination by microorganisms in cutting boards and the most suitable type for safe use. This article was developed through an integrative review of scientific articles found in electronic databases, Academic Google, PubMed and SciELO that addressed the microbiological analysis of cutting boards. The survey results showed the prevalence of mesophilic aerobic microorganisms, yeasts, fungi and bacteria of the Enterobacteriaceae family. To prevent cross-contamination in food, the use of colored polyethylene boards is recommended, where each color is designed for the preparation of a single type of food, in addition to not neglecting cleaning before and after using utensils.